The Jossey-Bass reader on educational leadership - Margaret Grogan (United States of America : Jossey-Bass, 2013)
These contributions cover all aspect of leadership from theory to practice, from values to characteristics of leaders, and from the past to future of leadership in society.
Part1. The principles of leadership -- Part2. Leadership for social justice -- Part3. Culture and Change -- Part4. Leadership for learning -- Part5. The future of leadership .
Includes bibliographical references and index.
Keywords: EDUCATIONAL LEADERSHIP; EDUCATIONAL LEADERSHIP -- UNITED STATES